Ambivalent Father Figures and the Enigma of Male Identity in Dickens’s Fiction - Max Véga-Ritter (Cahiers Victoriens et Edouardiens)
In a Freudian/gender approach to the issue of male sex identity in Charles Dickens’s fiction, the present article starts from Edmund Wilson’s seminal study ‘The Two Scrooges.’ It throws light on the way Dickens functioned in his earlier novels ambivalently or irresolutely, but alternately, on two opposite poles of his mind, those of self-identification with the benign—but eventually possibly inadequate—father image in the Pickwick Papers—the second Scrooge—or of a counter identification with its opposite negative image—the Rebels—in Oliver Twist, leaving the question of sex identity open or in a state of conundrum. Towards the end of Charles Dickens’s life, in Our Mutual Friend or in The Mystery of Edwin Drood, his fiction seems to present the reader with an image of the two Scrooges threatening to merge into one, hence the confusion about who the son is: a murderer or a murdered man. In some ways the Headstone-Wrayburn couple with its repressed homosexual undertones seems to function as an echo of that duplicity and uncertainty about the identity of the son. The first Scrooge seems to come very close to overcoming the second in that process. Eventually, the question of femininity and masculinity in male identity—the conundrum of sexual identity—seems to be still more at the heart of Charles Dickens’s fiction.